Chayote (Sechium edule) Peel Extracts: A Source of Bioactive Compounds for Cosmeceutical Design - Elsa F. Vieira; Pamela Ramirez; Ana Correia; Cristina Delerue-Matos (Biology and Life Sciences Forum, 2025)
This study explores the nutritional and economic potential of chayote (Sechium edule) peels (Cps) by extracting bioactive compounds using ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), and maceration (ME) techniques. Among these methods, UAE was the most effective, yielding the highest levels of phenolics and carotenoids, along with superior in vitro antioxidant activity. The UAE-derived extract displayed a low cytotoxicity on keratinocyte (HaCaT) cells. Furthermore, a stable gel formulated with the UAE-Cp extract exhibited excellent stability and promising cosmeceutical properties, highlighting the potential for the sustainable utilization of chayote peel waste in skincare applications.